2009
DOI: 10.1080/08860220902779962
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intravenous Anesthetics on Renal Ischemia/Reperfusion Injury

Abstract: Background. Renal ischemia/reperfusion (I/R)-induced tubular epithelial cell injury, called ischemic acute renal failure, is associated with high mortality in humans. Protecting the kidney against I/R injury is very important during complicated renal operations, transplantation surgery, and anesthesia. Aim. The purpose of this study was to investigate and compare the efficiency of ketamine, thiopental, propofol, etomidate, and intralipid in reducing the injury induced by free radicals in a rat model of renal I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 17 publications
0
32
1
2
Order By: Relevance
“…Thiopental is a highly lipid-soluble anesthetic, which has indicated antioxidant effect by inhibiting lipid peroxidation in ischemia/reperfusion injury [17] . Protective effects of thiopental for renal ischemia/reperfusion injury was searched in several and compared with the other intravenous agents [13,17,23] . Yüzer et al [13] reported that propofol and thiopental anesthesia protects against biochemical, and morphological damage better than control in renal I/R injury.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thiopental is a highly lipid-soluble anesthetic, which has indicated antioxidant effect by inhibiting lipid peroxidation in ischemia/reperfusion injury [17] . Protective effects of thiopental for renal ischemia/reperfusion injury was searched in several and compared with the other intravenous agents [13,17,23] . Yüzer et al [13] reported that propofol and thiopental anesthesia protects against biochemical, and morphological damage better than control in renal I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…Protective effects of thiopental for renal ischemia/reperfusion injury was searched in several and compared with the other intravenous agents [13,17,23] . Yüzer et al [13] reported that propofol and thiopental anesthesia protects against biochemical, and morphological damage better than control in renal I/R injury. They also reported in the same study; thiopental decreases the kidney I/R damage via free oxygen radicals in rats, and this effect is significant compared to etomidate [13] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[8] Simultaneously, the release of oxygen free radicals and proteolytic enzymes may cause large numbers of oxygen free radicals again and more serious organ damage. [9] This may be an important mechanism that causes pancreatic injury and induces MODS in the process of ARF.…”
Section: Tablementioning
confidence: 99%